Market intervention policies for increasing the consumption of nutrients by low income households - Perrin, Richard K.; Scobie, Grant McDonald (Wiley, 1981)
This study employs a market equilibrium displacement approach to examine the nutrient consumption effects of market intervention programs such as food subsidies, income transfers, and agricultural input subsidies. The results permit comparison of the direct treasury costs of achieving marginal increases in nutrient intake with alternative programs. When applied to a case study of the food markets and population of Cali, Colombia, it was found that a marginal increase in caloric intake among the poor could be achieved at lowest cost with a consumer subsidy of certain cereals, although black market activity might raise this cost to that of an income subsidy.